Effect of Maternal use of Labetalol on the Cerebral Autoregulation in Premature Infants (2013)
Hypertensive disorders of pregnancy (HDP) are normally treated to avoid maternal complications. In this study we aimed to investigate if there was an effect of maternal HDP treatment on the cerebral autoregulation of the neonates by analysing measurements of mean arterial blood pressure (MABP) and rScO2 by means of correlation, coherence, and transfer function analysis. We found that these infants presented higher values of transfer function gain, which indicates impaired cerebral autoregulation, with a decreasing trend towards normality. We hypothesised that this trend was due to a vasodilation effect of the maternal use of labetalol due to accumulation, which disappeared by the third day after birth. Therefore, we investigated the values of pulse pressure in order to find evidence for a vasodilatory effect. We found that lower values of pulse pressure were present in these infants when compared with a control population, which, together with increased transfer function gain values, suggests an effect of the drug on the cerebral autoregulation.